Educational needs of female adolescents regarding reproductive health: A case study in Hamadan-Iran - Seyedeh Zahra Masoumi; Farideh Kazemi; Fatemeh Delforouz; Maryam Kousha; Javad Faradmal; Javad Faradmal (Journal of Research & Health, 2017)
Due to the evolutionary nature of adolescence period and its specific characteristics and needs, assessment of adolescents’ health needs is of great importance. The present study aimed to determine educational needs of female high school students regarding reproductive health. This study was conducted on female high school students in Hamadan, Iran. The study participants included 346 students selected through cluster sampling. The study data were collected using modified WHO’s questionnaire. The results showed that 80.4% of the participants had weak to moderate knowledge about nutrition, 54.9% about anatomy, 94.2% about physiology, 85.6% about menstrual health, 93.9% about common cancers among women, 89.9% about genetics, 15.9% about puberty, 72% about STD/HIV, and 48.9% about contraception. The study results revealed the necessity of training in various areas of reproductive health in female high school students.